Improving Tribological Behavior of ICE’s Cylinder Surface by Laser Surface Texturing (LST) - Tripathi, K.; Lee, S. W. (Journal of Nepal Physical Society, 2021)
This study investigates the effect of laser surface texturing (LST) on the friction and wear behavior of grey cast iron (GCI) of internal combustion engine (ICE) cylinder in lubricated conditions. The dimples having diameter of about (58-60) μm and depth of about 10 μm were created on the surface with various dimple densities ranging from 5 to 50%. A ball-on-disc friction tests were performed for all the specimens under 5W30 and 15W50 oils with different viscosities. The tests were carried out at a load of 5N and speed of 5cm/s. The coefficient of friction of the dimpled specimen was reduced significantly by approximately 32% as compared to the polished speciemen. Specimen with 15% dimples exhibits the lowest coefficient of friction of all the dimpled specimens in both low and high viscous oils. The high viscous oil found to be more efficient regarding coefficeint of friction compared to the low viscous oil. The degree of wear of the specimens was analyzed on the basis of wear scar developed on the counter surface as it supplements the wear during the friction tests. The resistance to wear of the sliding specimens was found to be increased in high viscous oil compared to that in low viscous oil.